Assessing and Developing the Application of LEED Green Building Rating System as a Sustainable Project Management and Market Tool in the Italian Context - Walaa S. E. Ismaee (Journal of Engineering, Project, and Production Management, 2016)
The paper discusses the recent introduction of the LEED system to the Italian context in order to assess its role to promote sustainable building process in the Italian context, pointing out its potentials on one hand as well as their gaps and limitations on the other hand, and suggests means for its future development. The study discusses the application of LEED as a ‘Sustainable Project management tool’ to guide sustainable building performance. This requires investigating the following: its structure, tools, assessment criteria along with its benchmarks and references. It also discusses the application of LEED as a ‘Sustainable building Certification and market tool’. This investigates the role and value of the LEED certification in the Italian Green market.